A Resource for E-Moderators on Fostering Participatory Engagement Within Discussion Boards for Online Students in Higher Education. - Payne, Ameena L. (Student Success v.12 n.1 p.93-101 https://doi.org/10.5204/ssj.1865, 2021)
Through the lens of the 'Community of Inquiry' education experience (Vaughan & Garrison, 2006), this practice report provides guidance and examples for online instructors to engage students within discussions in the digital realm. Five elements will be discussed: embedding multi-media, affiliative humour and storytelling, Socratic questioning, 'reframes' and, summarising and 'weaving'. Based on the lived experience of one eLearning Advisor, or online instructor/e-moderator, at Swinburne Online, this practice report offers useful strategies to build engaging, sustainable learning conversations within discussion forums that are abundant with collaborative inquiry, dialogue and sharing of personal learning experiences for online students in higher education. [Author abstract]